2021
DOI: 10.21837/pm.v19i16.948
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of a Malaysia Modern Rural Development Framework: Synergising Rural for Change

Abstract: Malaysian government aims to transform rural areas into economic focal points, improves rural livelihoods, living environment and narrows the life quality gaps between those living in urban and rural areas. Inspired by the government directive-aspirations and the emergence of new technologies in national and global rural practices, this paper attempts to discuss the formulation of a framework for rural development in Malaysia based on a modern approach. The process undertakes two main stages, namely focused li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…Rural lifestyle changes have an adverse influence on the emergence of social and economic inequality within rural communities (Vorobyov & Bugai 2019, Liu et al 2020, Rashid et al 2021. This is consistent with a study conducted by Ziwei Qi (2019), which found that changes in lifestyle lead to gender inequality in access to resources and services.…”
Section: Introductionsupporting
confidence: 86%
“…Rural lifestyle changes have an adverse influence on the emergence of social and economic inequality within rural communities (Vorobyov & Bugai 2019, Liu et al 2020, Rashid et al 2021. This is consistent with a study conducted by Ziwei Qi (2019), which found that changes in lifestyle lead to gender inequality in access to resources and services.…”
Section: Introductionsupporting
confidence: 86%
“…For example, the use of GPS and precision farming techniques has enabled more efficient and sustainable agricultural practices (Putri et al, 2015;Rehman & Hussain, 2016). Furthermore, the use of electronic record storage and inventory management systems has allowed agritourism businesses to more easily track and analyze data related to their operations (Mpiti & de la Harpe, 2016;Rashid et al, 2021). However, the use of ICT in agritourism is not without its challenges.…”
Section: Managementmentioning
confidence: 99%
“…One issue is the potential for a digital divide, where smaller or less technologically advanced agritourism businesses may be at a disadvantage (Martin et al, 2015). Additionally, there are concerns about the potential for ICT to replace personal interaction and hands-on experience, which are often valued by agritourism customers (Rashid et al, 2021).…”
Section: Managementmentioning
confidence: 99%
“…By aligning with SDGs, Malaysian agrotourism real estate investments can contribute to addressing social inclusion challenges. Agrotourism programmes can empower local communities by providing employment opportunities and promoting cultural preservation through heritage tourism initiatives [1]. In addition, it is crucial that these initiatives prioritise inclusive practices that promote gender equality, accessibility for people with disabilities, and respect for indigenous rights.…”
Section: Social Inclusionmentioning
confidence: 99%
“…Given the country's abundance of fertile land and other resources, agrotourism in Malaysia has great potential. There is a wide variety of agricultural attractions in Malaysia that could attract visitors from all over the world, such as the lush tea gardens in the Cameron Highlands, the bright tropical fruit orchards in Penang, and the pepper farms in Sarawak [1].…”
Section: Introductionmentioning
confidence: 99%